Missing The Forest For The Trees: A Lack Of Upper Extremity Physical Performance Testing In Sports Physical Therapy - Matthew L Gauthier; Casey A Unverzagt; Luciana De Michelis Mendonça; Amee L Seitz (International Journal of Sports Physical Therapy)
# Background